THE INFLUENCE OF THE SOCIO-ECONOMIC FACTOR ON DISTINCTIVE FEATURES OF “UKRAINIZATION” IN DONBAS IN THE 20s–30s OF THE 20th CENTURY - Сергієнко, Сергій (SWorldJournal, 2024)
The article studies the influence of the socio-economic factor on distinctive features of “Ukrainization” in Donbas based on literature, periodicals, and archival sources. It is noted that this factor significantly influenced “Ukrainization” in the region